2022
DOI: 10.3390/plants11202680
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Natural Deep Eutectic Solvents Extraction of Bilberry Anthocyanins: Optimization, Bioactivities, and Storage Stability

Abstract: Bilberry fruits (Vaccinium myrtillus L.) are one of the richest natural sources of anthocyanins and are widely used due to their pharmacological and nutritional properties. To ensure their maximum application potential, it is necessary to overcome the limitations of conventional extraction solvents and techniques. This study aimed to develop a green method for bilberry anthocyanin extraction using natural deep eutectic solvents (NaDES) integrated with ultrasound-assisted extraction (UAE) in order to define ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The results showed that choline chloride:sorbitol (1:1) was the most efficient extraction solvent. Thecyanoglyco-3-o-glucoside yield was 0.2751 mg/g DW and the TAC yield was 2.12 mg CGE/g under optimal extraction conditions (37.63 min, 48.38 • C, 34.79% (w/w) water in NADES) [15]. DES extracted polyphenols, carbohydrates and lipids and could be employed for food safety monitoring and biosensor development as a feasible alternative.…”
Section: Combined Extraction Methodsmentioning
confidence: 99%
“…The results showed that choline chloride:sorbitol (1:1) was the most efficient extraction solvent. Thecyanoglyco-3-o-glucoside yield was 0.2751 mg/g DW and the TAC yield was 2.12 mg CGE/g under optimal extraction conditions (37.63 min, 48.38 • C, 34.79% (w/w) water in NADES) [15]. DES extracted polyphenols, carbohydrates and lipids and could be employed for food safety monitoring and biosensor development as a feasible alternative.…”
Section: Combined Extraction Methodsmentioning
confidence: 99%
“…Jovanović et al developed a NADES-based extraction process for elderberry anthocyanins. The study showed that anthocyanins extracted using a ChCl/xylitol NADES exhibited the highest antioxidant and antimicrobial activities and had better stability [20]. Moreover, the acidity of the solution can affect the extraction efficiency of anthocyanins.…”
Section: Extraction Of Anthocyaninsmentioning
confidence: 99%
“…Therefore, they can effectively extract polar or non-polar components from plants. They have been widely used to extract natural active substances from plants, such as polysaccharides [ 29 ], flavonoids [ 30 , 31 ], phenols [ 32 ], and anthocyanins [ 33 , 34 ]. They are more effective than traditional extraction solvents for extracting natural active molecules.…”
Section: Introductionmentioning
confidence: 99%